Intramolecular alkene-alkene coupling via Rh(III)-catalyzed alkenyl sp² C-H functionalization: divergent pathways to indene or α-naphthol derivatives - Maraswami, Manikantha (2022)
Highly selective synthesis of either indene or 1-naphthol derivatives through intramolecular alkene-alkene cross-coupling is reported. The reaction works with different alkene pairs that couple to give the corresponding products in good to satisfactory yields. The indene products of our reaction also allow further derivatization. The reaction pathway is dependent on alkene functionalities.